Tansy Davies Between Worlds, Barbican Theatre, London. (October 2015) - Miller, Malcolm
<x content-type="archive" xml:space="preserve">Abstract</x> As suggested by its title, Tansy Davies's new opera Between Worlds is more fantasy than a representational depiction of historic events. Co-commissioned by ENO and the Barbican, where it was premiered on 11 April 2015 with a superb cast conducted by Gerry Cornelius (I attended on 21 April), it raises a central aesthetic and political question about the extent to which public figures of our time can be drawn and re-drawn in art. Recent docu-operas, such as Nixon in China, the more recent Anna Nicole and, of course, the highly controversial The Death of Klinghoffer suggest the issue is a live one.